Analysis of Factors Affecting Compliance with Motor Vehicle Tax Payments at Integrated one Stop Administration System (SAMSAT) Sipirok - Siregar, Ayu Lestari; Syafina, Laylan; Nurwani, Nurwani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Motor vehicle tax serves as an important source of regional income. However, taxpayer compliance at the SAMSAT Sipirok remains relatively low, prompting the need for further research into the influencing factors. This study aims to analyze the effect of tax rates, tax knowledge, tax sanctions, and individual income both partially and simultaneously on motor vehicle taxpayer compliance at SAMSAT Sipirok. A quantitative method with a causal associative approach was employed. The research findings indicate that tax knowledge and individual income are the main factors driving taxpayer compliance. In contrast, tax rates and tax sanctions have not played an optimal role in enhancing compliance, as their implementation is considered neither strict nor consistent. Overall, the research model suggests that taxpayer compliance is more strongly influenced by understanding and economic conditions than by tax rates or sanctions. These findings contribute to the development of policy strategies, particularly through strengthening tax education and addressing the economic conditions of society.